1995
DOI: 10.1177/0146167295218001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Positive Affect in Syllogism Performance

Abstract: Previous research has found that people in positive moods perform better than others on creativity and divergent thinking tasks but perform more poorly and/or process the available information less thoroughly on many other cognitive tasks. The present experiment examined various hypotheses concerning the process mediating the latter effect. Positive mood subjects performed significantly worse on a set of syllogisms than control subjects, even though they had ample timefor the task. Positive mood subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 10 publications
3
61
2
3
Order By: Relevance
“…The participants in both positive and negative moods were less likely to provide the normatively correct answers, compared with the control group. Melton (1995) found analogous effects of positive mood on a syllogistic reasoning task. Again, participants in a positive mood were less likely to provide logically valid answers, compared with the control group.…”
Section: Emotion and Reasoning: Empirical Findingsmentioning
confidence: 79%
“…The participants in both positive and negative moods were less likely to provide the normatively correct answers, compared with the control group. Melton (1995) found analogous effects of positive mood on a syllogistic reasoning task. Again, participants in a positive mood were less likely to provide logically valid answers, compared with the control group.…”
Section: Emotion and Reasoning: Empirical Findingsmentioning
confidence: 79%
“…To the extent that stereotypes constitute ''rules of thumb'' meant to save the time and energy required to process individuating information (Macrae, Milne, & Bodenhausen, 1994), these findings are also consistent with the notion that negative, relative to positive affective states, promote expenditure of cognitive effort, in this case inhibiting the use of heuristics involving category membership. Parallel findings have also emerged from the domain of problem solving, where it has been shown that individuals in negative affective states exhibit superior performance on a range of tasks that demand careful, effortful processing (e.g., correlation estimation, Sinclair & Mark, 1995;logical reasoning, Fiedler, 1988), whereas those in positive affective states exhibit impaired performance on such tasks (e.g., Fiedler, 1988;Isen, Means, Patrick, & Nowicki, 1982;Melton, 1995;Sinclair & Mark, 1995). Together, these findings, and others, offer strong converging support for the core predictions of the feelings-as-information framework.…”
mentioning
confidence: 82%
“…In fact, it may be that earlier findings that seemed to suggest that positive affect impaired careful processing (e.g., Mackie & Worth, 1989;Melton, 1995;Schwarz & Bless, 1991) could have been a function of the particular materials and task situations involved. An ongoing study is currently investigating this possibility (Isen, Christianson, & Labroo, 2001).…”
Section: Decision Makingmentioning
confidence: 97%